Prevalence of malocclusion in people with disabilities - Cuoghi, Osmar Aparecido; Faria, Lorraine Perciliano; Micheletti, Kelly Regina; Miranda-Zamalloa, Yesselin Margot; de Mendonça, Marcos Rogério (Brazilian Dental Science, 2016)
Objective: To evaluate the prevalence of malocclusion in patients with disabilities. Material and Methods: The sample consisted in 98 patients of who had a previous diagnosis of disability. Patientes were divided into three groups: Intelectual Disabilities (ID), Cerebral Palsy (CP) and Down Syndrome (DS). They were evaluated according to Angle malocclusion classification, presence or absence of posterior crossbite, anterior crossbite and anterior open bite. Statistical analysis of the data was performed using the Kruskal Wallis test at 5% significance level. Results: Class II malocclusion was more frequent in the three groups (CP 45.45%, ID 40.43% and DS 50.00%); the anterior and the posterior crossbite were more prevalent in DS (p < 0.0001). The anterior open bite was more prevalent in CP (p < 0.0001). Conclusion: Patients with disabilities have high rate of malocclusion and understanding this condition is essential to establish appropriate treatment. Keywords: Orthodontics; Malocclusion; People with disabilities.